If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 47 = 114 Reorder the terms: 47 + x = 114 Solving 47 + x = 114 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + x = 114 + -47 Combine like terms: 47 + -47 = 0 0 + x = 114 + -47 x = 114 + -47 Combine like terms: 114 + -47 = 67 x = 67 Simplifying x = 67
| 6.8+k=6.8+k | | 1/4x-2y=-3/4 | | 3(6x-2)=180 | | X+(x+6499)=210355 | | 1.5t+6=7 | | 7x+10=5z-9 | | -7x+7(-2+10)=-56 | | 12x-8=2x+42 | | A1/2=-5-12 | | 15/2h=5/12 | | 8/16÷5/39 | | (-30)=w+(-14) | | -7+5x=-43 | | -2-4x+6-5x=-9x-4 | | 19x+13y=3 | | -5+2x=12 | | 3x-3(2x-6)=-6 | | n/2-12=2 | | 3x+2x=-5x-10 | | -4(7x-1)=-24 | | 35=b+17 | | 1.5+6=7 | | 8x^3/x-5 | | 8-14z=-24+12z | | 9x+10y=145 | | 7t-2+3t+1=-3+9t | | 2x-10+8x=30 | | 5x-7(-2x-13)=-61 | | 54/8=8/n | | 2/3x-9=3/4 | | A+2=(-11) | | Cx+11y=3 |